Pericentric inversion of human chromosome 9 epidemiology study in Czech males and females - Šípek, Antonín; Panczak, Aleš; Mihalová, Romana; Hrčková, Lenka; Suttrová, E; Sobotka, Vladimír; Lonský, Petr; Kaspříková, Nikola; Gregor, Vladimír (Folia biologica (Praha), 2015)
Pericentric inversion of human chromosome 9 [inv(9)] is a relatively common cytogenetic finding. It is largely considered a clinically insignificant variant of the normal human karyotype. However, numerous studies have suggested its possible association with certain pathologies, e.g., infertility, habitual abortions or schizophrenia. We analysed the incidence of inv(9) and the spectrum of clinical indications for karyotyping among inv(9) carriers in three medical genetics departments in Prague. In their cytogenetic databases, among 26,597 total records we identified 421 (1.6 %) cases of inv(9) without any concurrent cytogenetic pathology. This study represents the world's largest epidemiological study on inv(9) to date. The incidence of inv(9) calculated in this way from diagnostic laboratory data does not differ from the incidence of inv(9) in three specific populationbased samples of healthy individuals (N = 4,166) karyotyped for preventive (amniocentesis for advanced maternal age, gamete donation) or legal reasons (children awaiting adoption). The most frequent clinical indication in inv(9) carriers was "idiopathic reproductive failure" - 37.1 %. The spectra and percentages of indications in individuals with inv(9) were further statistically evaluated for one of the departments (N = 170) by comparing individuals with inv(9) to a control group of 661 individuals with normal karyotypes without this inversion. The proportion of clinical referrals for "idiopathic reproductive failure" among inv(9) cases remains higher than in controls, but the difference is not statistically significant for both genders combined. Analysis in separated genders showed that the incidence of "idiopathic reproductive failure" could differ among inv(9) female and male carriers.
Keywords: cytogenetika; Adolescent; chromozomální inverze; Karyotyping; Child; Cytogenetics; lidé; Female; mužské pohlaví; Chromosome Inversion; lidské chromozomy, pár 9; dítě; Male; karyotypizace; mladiství; Chromosomes, Human, Pair 9; ženské pohlaví; Humans